Fundamentals of Cheese Science - Fox, Patrick F.; Guinee, Timothy P.; Cogan, Timothy M.; McSweeney, Paul L. H.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2017)
This book provides comprehensive coverage of the scientific aspects of cheese, emphasizing fundamental principles. The book's updated 22 chapters cover the chemistry and microbiology of milk for cheesemaking, starter cultures, coagulation of milk by enzymes or by acidification, the microbiology and biochemistry of cheese ripening, the flavor and rheology of cheese, processed cheese, cheese as a food ingredient, public health and nutritional aspects of cheese, and various methods used for the analysis of cheese. The book contains copious references to other texts and review articles.
Cheese: Historical Aspects -- Overview of Cheese Manufacture -- Principal Families of Cheese -- Chemistry of Milk Constituents -- Bacteriology of Cheese Milk -- Starter Cultures -- Enzymatic Coagulation of Milk -- Post-Coagulation Treatment of the Renneted-Milk Gel -- Salting of Cheese Curd -- Cheese Yield -- Microbiology of Cheese Ripening -- Biochemistry of Cheese Ripening -- Cheese Flavour -- Cheese: Structure, Rheology and Texture -- Factors That Affect Cheese Quality -- Fresh Cheese Products: Principals of Manufacture and Overview of Different Varieties -- Processed Cheese and Substitute/Imitation Cheese Products -- Ingredient Cheese and Ingredients Derived from Cheese -- Pathogens and Foodborne Illness in Cheese -- Nutritional Aspects of Cheese -- Current legislation on cheese -- Chapter 22: Whey and Whey Products.
Keywords: Food science; Food -- Microbiology; Bacteria; Food Science; Food Microbiology; Bacteria